The internal syntax of adjectival quantification in Romance - Martinho, Fernando (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2020)
The theoretical framework of this paper is based on the Extended Adjectival Projection hypothesis first introduced by Corver (1997). In Absolute Measure Phrase constructions (AMPC), of the “2m tall” type, we argue that, in the Romance equivalent “alto de 2m”, the adjective first merges with the functional item ‘de’, and then with an inflected functional head, above the MP position. As there is independent motivation that this position is [Spec, QAP], we consider ‘de’ as a spell-out of the functional quantifier head QAº. We propose the Adjectival Linker Hypothesis (ALH), in which ‘de’ is a binding particle whose function is to allow the projection of absolute measurement expressions in Romance gradable adjectives syntax. The data resulting from the insertion of ‘de’ is then crossed with other adjectival expressions in Romance, Germanic and Scandinavian, in which the QA position is alternatively filled by different QA spell-outs. Further Romance data is then confronted with some cases of pseudopartitive adjectival ‘de’ in a Small Clause like configuration. We finally introduce a MP parameter to justify how variations affect the adjectival expressions of measurement across languages, and how and why the functional head QA may be null or filled with ‘de’, therefore postulating a phonetically null form as one of its various spell-outs. In the absence of an absolute MP and its related ALH, QA is alternatively filled with regular, lexical spell-outs such as superlative suffixes or autonomous morphemes. Lastly, in the case of relative MP expressions, a functional head DegA is lexically filled with a degree morpheme, switching the whole adjectival expression to a comparative form.